2016
DOI: 10.1177/0886260516633692
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse and Antisocial Traits and Behaviors: A Gendered Examination of the Factors Associated With Perpetration of Intimate Partner Violence

Abstract: The current study addressed the relationship between child sexual abuse (CSA) and perpetration of physical intimate partner violence, examining the possible mediating effect of antisocial traits and behaviors, as well as the differences in these relationships between men and women. Data came from the International Dating Violence Study. Hypotheses were tested on a sample of 13,659 university students from 68 sites and 32 countries using hierarchical linear modeling. Results indicated that CSA was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 100 publications
2
16
1
1
Order By: Relevance
“…That is, a similar proportion of participants from each group reported the ACE of sexual abuse, parents separated/divorced, domestic violence in the home, and an incarcerated family member. Thus, despite differing behavioral manifestations, these results suggest that later adult violence, of any type, may be more likely when a female is raised within an abusive (i.e., especially sexually abusive), dysfunctional household (Cubellis, Peterson, Henninger, & Lee, 2016). Of the results obtained from this study, this particular finding offers an important consideration for future research.…”
Section: Discussionmentioning
confidence: 57%
“…That is, a similar proportion of participants from each group reported the ACE of sexual abuse, parents separated/divorced, domestic violence in the home, and an incarcerated family member. Thus, despite differing behavioral manifestations, these results suggest that later adult violence, of any type, may be more likely when a female is raised within an abusive (i.e., especially sexually abusive), dysfunctional household (Cubellis, Peterson, Henninger, & Lee, 2016). Of the results obtained from this study, this particular finding offers an important consideration for future research.…”
Section: Discussionmentioning
confidence: 57%
“…However, these relationships were not statistically significant among women. Previous studies have found that childhood sexual abuse is positively associated with IPV perpetration among men and women but the relationship has been found to be stronger for men [108]. Research has suggested that men, who are victims of childhood sexual abuse may be more likely to show aggression and violence against others, while women may be less likely to externalize their experience in the form of aggression and may be more likely to internalize their childhood sexual abuse experiences [108].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that childhood sexual abuse is positively associated with IPV perpetration among men and women but the relationship has been found to be stronger for men [108]. Research has suggested that men, who are victims of childhood sexual abuse may be more likely to show aggression and violence against others, while women may be less likely to externalize their experience in the form of aggression and may be more likely to internalize their childhood sexual abuse experiences [108]. Male perpetrators of physical and sexual IPV tend to engage in risky sexual behavior, including main partner infidelity [109], paying money for sex [109], less condom use [110], and are more likely to be diagnosed with HIV/STIs [77, 78].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, although substance abuse mediated the relationship between physical and psychological abuse and IPV for both genders, among men, posttraumatic stress disorder mediated the relationship between sexual abuse and later IPV. Similarly, a study using international dating violence data (Cubellis et al, 2018) examined the mediating effects of antisocial traits on the relationship between child sexual abuse and partner violence. They found antisocial traits and behaviors fully mediated the effects of child sexual abuse on violence for women, but only partially mediated the effects for men.…”
Section: Gender and Ipvmentioning
confidence: 99%
“…Research also consistantly finds that experiencing early childhood trauma (White & Widom, 2003), using alcohol and other substances (Stith, Smith, Penn, Ward, & Tritt, 2004), and having a personality disorder (Dutton, 2006) are associated with being violent toward a romantic partner. However, gender differences in the roles of these characteristics have also been found (e.g., child sexual abuse—Fang & Corso, 2008; alcohol use—Foshee, Linder, MacDougall, & Bangdiwala, 2001; and psychopathology—Dowgwillo, Ménard, Krueger, & Pincus, 2016; Ehrensaft, Moffitt, & Caspi, 2004), suggesting gendered pathways to IPV may exist (Cubellis, Peterson, Henninger, & Lee, 2018; Jung et al, 2017). Legislation including Title IX, the Department of Education Dear Colleague Letter of 2011, and the 2013 Campus Sexual Violence Elimination Act, has been enacted requiring educational institutions (e.g., colleges) investigate and respond to crimes of interpersonal violence (e.g., sexual assault, stalking, dating violence) on campus.…”
mentioning
confidence: 99%